WFCatalog: A catalogue for seismological waveform data. (September 2017) - Trani, Luca; Koymans, Mathijs; Atkinson, Malcolm; Sleeman, Reinoud; Filgueira, Rosa
Abstract: This paper reports advances in seismic waveform description and discovery leading to a new seismological service and presents the key steps in its design, implementation and adoption. This service, namedWFCatalog, which stands for waveform catalogue, accommodates features of seismological waveform data. Therefore, it meets the need for seismologists to be able to select waveform data based on seismic waveform features as well as sensor geolocations and temporal specifications. We describe the collaborative design methods and the technical solution showing the central role of seismic feature catalogues in framing the technical and operational delivery of the new service. Also, we provide an overview of the complex environment wherein this endeavour is scoped and the related challenges discussed. As multi-disciplinary, multi-organisational and global collaboration is necessary to address today's challenges, canonical representations can provide a focus for collaboration and conceptual tools for agreeing directions. Such collaborations can be fostered and formalised by rallying intellectual effort into the design of novel scientific catalogues and the services that support them. This work offers an example of the benefits generated by involving cross-disciplinary skills (e.g. data and domain expertise) from the early stages of design, and by sustaining the engagement with the target community throughout the delivery and deployment process. Abstract : Highlights: Announcing a new seismology service for automated methods. Agreements on describing the quality of seismic data. Efficient software to extract the quality metrics. Demonstrable savings for practicing seismology researchers.